Friends’ Influence and Social Interaction on Callous-Emotional Trait of Adolescents: Does Neighborhood Characteristics Play Some Roles? - Ugwu, Paschal Chukwuma (Practicum Psychologia, 2024)
The study explored the moderating role of neighbourhood disorder on the relationship between friends’ influence and social interaction on callous-unemotional traits among 323 adolescents selected from secondary schools in Awka, AnambraState, Nigeria. The ages of the participants ranged from 14 – 17 with the mean age of 15.3 and standard deviation of 1.4. Their gender consisted of males 158 (48.9%) and females 165 (51.1%). Four instruments were used for data collection namely: parents and peer influence scale, social interaction scale, neighbourhood disorder scale and anti-social screening device. The study adopted cross sectional survey design and moderated regression statistics was used for data analysis. Four hypotheses were tested and the results showed that social interaction significantly and positively predicted callous-unemotional traits. Friends influence significantly and negatively predicted callous-unemotional traits. Also, neighbourhood disorder significantly and positively predicted callous-unemotional traits. Neighbourhood disorder significantly and positively moderated relation between social interaction and callous-unemotional traits. However, neighbourhood disorder did not moderate relation between friends’ influence and callous-unemotional traits. Thus, interventions aimed to reduce callous-unemotional traits should prioritize and promote cordial interpersonal relationship among adolescents.